Hippo/TEAD4 signaling pathway as a potential target for the treatment of breast cancer - Wu, Yujian (Oncol Lett, 2021)
Breast cancer is the most common type of cancer among women worldwide. The Hippo signaling pathway is strongly associated with cell proliferation, migration, invasion, metastasis and resistance to breast cancer treatment. The upstream factors involved in the Hippo signaling pathway, including mammalian Ste20 kinases 1/2, large tumor suppressor kinases 1/2 and transcription coactivator Yes-associated protein (YAP)/transcriptional coactivator with PDZ-binding motif (TAZ), have been extensively studied as they are considered therapeutic targets for breast cancer. Recently, it has been suggested that the transcriptional enhancer factor domain (TEAD) family of transcription factors, particularly TEAD4, plays an important role in breast cancer. TEADs interact with YAP/TAZ to act as transcription factors. Notably, recent studies have demonstrated that TEAD4 may also function in a YAP/TAZ-independent manner and serve as a prognostic marker for breast cancer. The present review summarizes the current research on the effect of the aberrant activation of the Hippo signaling pathway on breast cancer progression. Furthermore, the latest advances on the role of the TEAD family in breast cancer are highlighted, and the role of TEAD4 as a potential target for therapeutic intervention in breast cancer is discussed.